MODEL PEMBACAAN KRITIS TEKS-TEKS KEISLAMAN KAUM FEMINIS - Azzuhri, Muhandis (IAIN Pekalongan, 2014)
Abstract : Study feminism can not be separated from theological studies. Almost all religions have bad treatments against women. The position of women in some religions are placed as